Spectroscopic studies of Er3+-Yb3+ codoped multicomposition tellurite oxide glass - Baki, Sharudin Omar; Tan, L.S.; Kan, C.S.; Mohamed Kamari, Halimah; Muhammad Noor, Ahmad Shukri; Mahdi, Mohd Adzir (Trans Tech Publications, 2014)
Multicomposition of Er3+-Yb3+ codoped tellurite oxide, TeO2-ZnO-PbO-TiO2-Na2O glass has been investigated. Detailed spectroscopic study of the Judd-Ofelt analysis has been performed from the measured absorption spectrum in order to obtain the intensity parameters Wt (t=2, 4, 6). The calculated Wt values were then utilized in the determination of transition probabilities, radiative lifetimes and branching ratios of the Er3+ transitions between the J(upper)-J’(lower) manifolds. Both visible upconversion and near-infrared spectra were characterized under the 980 nm laser diode excitation at room temperature.